Knowledge, Attitüde and Practice of Family Planning among Married Women in Akinyele Local Government, Oyo State, Nigeria (2021)
The study examined knowledge, attitude and practice of family planning, among married women in Akinyele Local Government, Oyo State. The study adopted the descriptive survey research design. A total of 143 respondents participated in the study. The instrument employed was “Knowledge, Attitude and Practice of Family Planning, among Married Women Questionnaire”. The data collected from the study were analysed using simple percentage and mean to provide answers for the research questions raised for the study. Findings revealed that married women in Akinyele Local Government, Oyo State are aware of family planning (Mean= 2.99) but do not practice it (Mean=l .86). Findings further revealed that the married women in Akinyele Local Government, Oyo State portray negative attitude towards family planning (Mean=2.36). On this basis, the study recommended, among other things. that the government should endeavour to increase the level of awareness on the importance of family planning. ln addition, the mass media should also be encouraged to do more in terms of enlightening the public on the benefits of modern contraceptive methods as this will help married couples to portray positive attitude towards the use of family planning